(3OjhGf GdCOHs - (3ESMGb Hf EHQGgje Hf GdMSjf GdaGQGHqj, CHh EHQGgje, J (B350 (3g` s ((3CHh WGdH MeRI Hf YHO GdYRjR GdebTQi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf MeOkG jHdZ QVG hjeJQi GdeRjO efg CeG HYO hbO Cda GdSda (B_ (3QMege Gddg ai LeY gPG GddSGf cJHkG cKjQI s
(3BNQgG (B:s
(3ef HGH GdEaYdGd bhdg (B: (3d hGSeCd Ci VeQ , e (B: (3hGJdCe Gdbhe Ci GLJeYhG hGWHCf hGWeCf HeYfi hGMO , hCbSCf hGcHCf Ci EfbHV BNQ cJGH GdgeRI hgh BNQ cJGH OjhGf GdCOH hejRGf GddZI s
(3HgG fXGe GdJYbjHIs
(3HChdgG agGQS ddcJGHs
(3cJHJ HQSe CHj fLjL CMeO Hf GdMSjf Hf Ydi Hf OfQhjg GdbRhjfi GdTGaYis
(3fSNI NGeSI s
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
Keywords: (3GddZIs